Copy Detection of Multimedia Contents in Cloud (International Journal of Engineering and Computer Science, 2017)
: In Cloud, we describe the ways to enable protection of Multimedia contents from redistributing. Web has billions of documents including video, audio and images, but there is no central management system, where duplication of contents is more common . It is said that each and every document has a duplicate copy. This is more prevelant in videos stored in multiple formats, versions, size etc. and are found unaware by content creators when modified and republished using Video Editorial Tools.  This may lead to security problems and also reduplicating the identity of owners and also loss of revenue to content creators. This also occupies a enormous space over the web. In cloud storage too it is more common involving both public and private clouds. But the private cloud is said to be more secure when compared to the public cloud. So to avoid this situation some of the techniques have been used to avoid duplication of contents and focused mainly over the 3D-video contents.